Economic and technological feasibility of using power-to-hydrogen technology under higher wind penetration in China. (August 2021) - Lin, Haiyang; Wu, Qiuwei; Chen, Xinyu; Yang, Xi; Guo, Xinyang; Lv, Jiajun; Lu, Tianguang; Song, Shaojie; McElroy, Michael
Abstract: Hydrogen can play a key role in facilitating the transition to a future deeply decarbonized energy system and can help accommodate higher penetrations of renewables in the power system. Arguments to justify this conclusion are supported by an analysis based on real-world data from China's Western Inner Mongolia (WIM). The economic feasibility and decarbonization potential of renewable-based hydrogen production are discussed through an integrated power-hydrogen-emission analytical framework. The framework combines a high-resolution wind resource analysis with hourly simulation for the operation of power systems and hydrogen production considering technical and economic specifications on selection of three different types of electrolyzers and two operating modes. The results indicate that using wind power to produce hydrogen could provide a cost-competitive alternative (<2 kg −1 ) to WIM's current coal-dominated hydrogen manufacturing system, contributing at the same time to important reductions in wind curtailment and CO2 emissions. The levelized cost for hydrogen production is projected to decrease in the coming decade consistent with increases in wind power capacity and decreases in capital costs for electrolyzers. Lessons learned from the study can be applied to other regions and countries to explore possibilities for larger scale economically justified and carbon saving hydrogen production with renewables. Highlights: Propose an integrated power-hydrogen-emission analytical framework for H2 production. Conduct hourly system simulations with real data for Western Inner Mongolia China. Alkaline and solid oxide electrolyzers are the most cost-effective options for 2020 and 2030. Carbon-free H2 produced from wind power can be cost-competitive (0.5-2 /kg). An evidence of economic feasibility for renewable-based H2 production to other regions/countries.